Characterization of a collection of plasmid-containing bacteria isolated from an on-farm biopurification system used for pesticide removal - Martini, María Carla (2015)
Biopurification systems (BPS) are complex soil-related and artificially-generated environmentsusually designed for the removal of toxic compounds from contaminatedwastewaters.The present study has been conducted to isolate and characterize a collection of cultivableplasmid-carrying bacterial isolates recovered from a BPS established for thedecontamination of wastewater generated in a farmyard.Out of 1400 isolates, a collection of 75 plasmid-containing bacteria was obtained, ofwhich 35 representative isolates comprising in total at least 50 plasmids were chosen forfurther characterization. Bacterial hosts were taxonomically assigned by 16S ribosomal RNAgene sequencing and phenotypically characterized according to their ability to grow in presenceof different antibiotics and heavy metals. The study demonstrated that a high proportionof the isolates was tolerant to antibiotics and/or heavy metals, highlighting the on-farmBPS enrichment in such genetic traits. Several plasmids conferring such resistances in thebacterial collection were detected to be either mobilizable or selftransmissible. Occurrenceof broad host range plasmids of the incompatibility groups IncP, IncQ, IncN and IncWwas examined with positive results only for the first group. Presence of the IS1071 insertionsequence, frequently associated with xenobiotics degradation genes, was detected inDNA obtained from 24 of these isolates, strongly suggesting the presence of yet-hiddencatabolic activities in the collection of isolates. The results showed a remarkable diversityin the plasmid mobilome of cultivable bacteria in the BPS with the presence of abundantresistance markers of different types, thus providing a suitable environment to investigatethe genetic structure of the mobile genetic pool in a model on-farm biofilter forwastewater decontamination in intensive agricultural production.